Dream or Dilemma: The Unconscious Construction of the Modern House. Issue 2 (2nd July 2016) - Cavanagh, Ted
Abstract : Over time, balloon-frame construction has been debased, promoted, and then submerged into a collective cultural unconscious. In the nineteenth-century, diverse methods of house construction gradually combined into a single way of building. This created a "massive system"—a type of practice that technology historian Thomas Hughes describes as ubiquitous and resistant to change—including every point of material production to every scale of application, from forestry to urban design, including many unsustainable practices. How will things change? Either the system will adopt token improvements or there will be radical change, perhaps returning our ways of building to more diverse practices of construction. This article revisits material presented in this journal nearly twenty years ago, analyzing new data and introducing concepts of knowledge conversion, hybridity, and the social construction of technology to develop a history of wood framing that is rich and contingent, and that reveals, discusses, and elaborates implications of our indifferent use of light-wood frame construction.